2018
DOI: 10.1002/cncr.31637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an equal‐access military health system on racial disparities in colorectal cancer screening

Abstract: Within an equal-access, universal health care system, black patients had higher rates of CRC screening in comparison with prior reports and even in comparison with white patients within the population. These findings highlight the need to understand and develop meaningful approaches for promoting more equitable access to preventative care. Moreover, equal-access, universal health insurance for both the military and civilian populations can be presumed to improve access for underserved minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Racial disparities and access to medical care have been increasingly recognized as having a direct impact on disease presentation [20][21][22]. Furthermore, patients undergoing colorectal surgery requiring an ostomy typically use more health care resources and have the potential for more postoperative complications [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities and access to medical care have been increasingly recognized as having a direct impact on disease presentation [20][21][22]. Furthermore, patients undergoing colorectal surgery requiring an ostomy typically use more health care resources and have the potential for more postoperative complications [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare coverage does not equate to equitable delivery of care, and thus disparities in care delivery may be present within the MHS and contribute to both racial and SES/social class disparities in CKD. Prior research in the MHS has shown some care delivery disparities are present for some 6,31,32 but not other 33,34 care pathways in the MHS.…”
Section: Discussionmentioning
confidence: 95%
“…4,5 Universal healthcare coverage appears to mitigate racial and socioeconomic disparities across numerous health conditions. 6,7 Racial disparities in CKD often persist despite universal access to care, 7,8 and have been attributed to Black-white differences in the presence of high risk APOL1 variants. 8 However, socioeconomic disparities in CKD-which cannot be explained by genetic differences-are also apparent in settings with universal healthcare coverage, including the United Kingdom, Denmark and Australia.…”
Section: Introductionmentioning
confidence: 99%
“… 29 However, differences in demographic, social, and contextual factors between the UK primary care population and the MHS population must be acknowledged. The high rates of CKD coding in Black MHS beneficiaries is perhaps unsurprising, given that many Black-White health care disparities that persist in the United States are absent in the MHS, 30 , 31 , 32 , 33 perhaps due to the universal health care coverage provided through the MHS, the high rate of employment for MHS beneficiaries (or their sponsors), and/or differences in clinical cultures and practices.…”
Section: Discussionmentioning
confidence: 99%